Contributions of Indoor Household Activities to Inhalation Health Risks Induced by Gaseous Air Pollutants in Hong Kong Home - Lewei Zeng; Kaimin Li; Hai Guo; Beining Zhou; Xiaopu Lyu; Yunxi Huo; Erik Uhde; Jin Yang; Yangzong Zeren; Haoxian Lu; Dawen Yao; Zhe Qian (Aerosol and Air Quality Research)
Abstract To understand inhalation health risks at home, a comprehensive sampling campaign was conducted in a Hong Kong residential apartment from October to December 2019. Emissions of nine typical household activities, household background release and outdoor pollution were continuously monitored using a suite of the state-of-the-art instruments. Health risks were evaluated in each one-year exposure period. Acrolein and nitrogen dioxide (NO2) likely caused chronic non-carcinogenic risks to residents in all exposure stages. Furthermore, the health risk of the respiratory system was proved in all age groups. For the first time, several household activities were found to cause acute health risks due to exposure to formaldehyde, benzene, NO2 and acrolein in normal urban daily life. The probability distributions of cancer risks from household activities revealed that formaldehyde was the main carcinogen with an average risk of 2.00 × 10−4, followed by benzene, acetaldehyde, ethylbenzene and dichlorobenzene. Among all indoor activities, incense burning was the largest contributor to total cancer risk (46%), as this source was respectively responsible for 47%, 54%, and 39% of cancer risks from formaldehyde, benzene, and acetaldehyde, followed by cooking and smoking. Notably, source-related health risk analysis showed that household background release dominated regardless of cancer risk (35.7–58.5%) or non-carcinogenic risk (57.1%). Further, the cancer risk from birth to 18 years was approximately 1.8–2.7 times that of 18–60 and 60–85 years of age. This study shed light on health risks posed by various household activities and highlighted the importance of indoor activities and household background release on acute and chronic health risks.